Between construction and drawing: the Archive of the Barbieri Company of Castel Maggiore (BO) and the evolution of architectural technique - Vincenzo Petrillo (Disegnare con)
The technical archive of the Barbieri company, based in Castel Maggiore, represents a documentary source of extraordinary relevance for the study of construction developments between the 19th and 20th centuries. It effectively testifies to the activity of an industrial enterprise that operated for over a century in the fields of metal construction, applied mechanics, and refrigeration systems. A preliminary analysis of the graphic materials preserved in the archive – the only surviving ev¬idence after the flooding of the Navile stream – has brought to light several noteworthy projects, including drawings related to structural consoli¬dation, iron roofing, and theatrical structures. Among these stand out the works carried out for the Mercato delle Erbe in Bologna, the Apollo Theatre in Lecce, the stage of the Teatro Comunale in Bologna, the iron centring for the Palazzo del Podestà, and the bracing system for the Torre degli Asinelli. These projects, pertaining to both design and restoration, highlight the eclecticism of the workshop and its central role throughout its operational history, allowing us to reconstruct not only the technical solutions adopted but also the cultural and operational contexts in which they developed. Due to the quality and variety of its documen¬tation, the Barbieri Archive stands as an exem¬plary case of how corporate graphic production can become a subject of study and valorisation. Its preservation – now more urgent than ever – must involve structured processes of digitisation and cataloguing, in accordance with national regulations and the ministerial platforms for cultural heritage management. This study therefore seeks to foster a reflection on the historical and technical value of these materials, encouraging broader collaboration between public institutions and private entities for their conservation and accessibility. DOI: https://doi.org/10.20365/disegnarecon.34.2025.14